Practical Digital Image Processing with MATLAB - Nursuriati Jamil; Khalil Awang; Zaidah Ibrahim; Nurbaity Sabri; Rosniza Roslan; Nur Nabilah Abu Mangshor; Raseeda Hamzah (Pearson Prentice Hall, 2019)
This book is written for beginners and intermediate students, academicians and researchers in educational institutions and private sectors. The need for a practical introductory of understanding image processing concepts is crucial as practice in image processing applications requires a complete understanding of the mathematical concepts used in image processing and the ability to solve real-world problems in the most practical manner. In this second edition, examples of different domain applications such as plant leaf recognition and orchid identification are included with step-by-step instructions and MATLAB coding. Few classifiers used in the recognition and identification applications are also described.